Demographics, Clinical Characteristics, and Treatment Patterns in Patients with Psoriasis: Insights from the Saudi Arabia Psoriasis Registry (PSORSA) - Mohammad Ibrahim Fatani; Yousef Binamer; Hajer Y. Almudaiheem; Maysa Tariq Eshmawi; Fawaz Hamdi Aljehani; Sultanah Alshammari; Ahmed H. Al-Jedai (Dermatology and Therapy)
Abstract Introduction Psoriasis is a chronic immune-mediated inflammatory disease characterized by significant variability in clinical presentation and associated comorbidities. We aimed to describe the baseline demographic and clinical characteristics of patients with psoriasis enrolled in the Psoriasis Registry in Saudi Arabia (PSORSA). Methods This multicenter cohort study included patients with moderate-to-severe psoriasis from 40 hospitals in Saudi Arabia. Baseline demographics, clinical, and comorbidity data were collected and analyzed. Follow-up assessments were conducted every three months for one year. Results In total, 482 patients were enrolled. The mean age at diagnosis was 32.2 years, with a median disease duration of 848 days and a mean body mass index of 27.32 kg/m2. Male patients comprised 51.8% of the cohort, and 96.5% were Saudi nationals. A positive family history of psoriasis was reported in 17.2% of the participants. A total of 83 patients (17.2%) were documented to have comorbidities. Among these 83 patients, 47 (56.6%) had psoriatic arthritis, 20 (24.1%) had diabetes, and 14 (16.9%) had hypertension. Plaque psoriasis was the most common subtype (94.2%), and the most affected body regions were the upper and lower extremities (88.1% and 85.5%, respectively), followed by the scalp and trunk (75.7% each). The mean PASI score at baseline was 25 ± 13.3, which decreased to 0.32 ± 0.94 by week > 52. Conventional systemic therapies were prescribed to 22.6% of the patients, with methotrexate being the most common agent (18%). Biologic therapies were prescribed to 28.9% of the patients, with adalimumab being the most commonly used (21%). In addition, 12.7% of the cohort received phototherapy. Adverse events occurred in 2.1% of the patients, with cyclosporine contributing to 25% of the reported events. Conclusion The PSORSA registry provides valuable insights into the demographics, clinical characteristics, and treatment patterns of patients with psoriasis in Saudi Arabia. These findings emphasize the need for real-world data to guide regional psoriasis management strategies.